Efficacy of neural stem cell transplantation for the treatment of patients with spinal cord injury: A protocol of systematic review and meta-analysis - Tang, Hua-yu (Medicine (Baltimore), 2020)
BACKGROUND: The aim of this study is to evaluate the efficacy of neural stem cell transplantation (NSCT) for the treatment of patients with spinal cord injury (SCI). METHODS: All potential randomized controlled trials (RCTs) on NSCT in the treatment of patients with SCI will be searched from the following electronic databases: Cochrane Library, MEDILINE, EMBASE, Web of Science, Scopus, CBM, WANGFANG, and CNKI. We will search all electronic databases from their initiation to the January 31, 2020 in spite of language and publication date. Two contributors will independently select studies from all searched literatures, extract data from included trials, and evaluate study quality for all eligible RCTs using Cochrane risk of bias tool, respectively. Any confusion will be resolved by consulting contributor and a consensus will be reached. We will utilize RevMan 5.3 software to pool the data and to conduct the data analysis. RESULTS: This study will summarize the most recent RCTs to investigate the efficacy and safety of NSCT in the treatment of patients with SCI. CONCLUSION: This study will provide evidence to assess the efficacy and safety of NSCT in the treatment of patients with SCI at evidence-based medicine level. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42020173792.